The Neisseria gonorrhoeae Methionine Sulfoxide Reductase (MsrA/B) Is a Surface Exposed, Immunogenic, Vaccine Candidate - Jen, Freda E.-C.; Semchenko, Evgeny A.; Day, Christopher J.; Seib, Kate L.; Jennings, Michael P. (Frontiers in Immunology, 2019)
Control of the sexually transmitted infection gonorrhoea is a major public health challenge due to the recent emergence of multidrug resistant strains of Neisseria gonorrhoeae, and there is an urgent need for novel therapies or a vaccine to prevent gonococcal disease. In this study, we evaluated the methionine sulfoxide reductase (MsrA/B) of N. gonorrhoeae as a potential vaccine candidate, in terms of its expression, sequence conservation, localization, immunogenicity, and the functional activity of antibodies raised to it. Gonococcal MsrA/B has previously been shown to reduce methionine sulfoxide (Met(O)) to methionine (Met) in oxidized proteins and protect against oxidative stress. Here we have shown that the gene encoding MsrA/B is present, highly conserved and expressed in all N. gonorrhoeae strains investigated, and we determined that MsrA/B is surface exposed on N. gonorrhoeae. Recombinant MsrA/B is immunogenic, and mice immunized with MsrA/B and either aluminium hydroxide gel adjuvant or Freund's adjuvant generated a humoral immune response, with predominantly IgG1 antibodies. Higher titres of IgG2a, IgG2b and IgG3 were detected in mice immunized with MsrA/B-Freund’s adjuvant compared to MsrA/B-aluminium hydroxide adjuvant, while IgM titres were similar for both adjuvants. Antibodies generated by MsrA/B-Freund’s in mice mediated bacterial killing via both serum bactericidal activity and opsonophagocytic activity. Anti-MsrA/B was also able to functionally block the activity of MsrA/B by inhibiting binding to its substrate, Met(O). We propose that recombinant MsrA/B is a promising vaccine antigen for N. gonorrhoeae.